FAIR as a journey: lessons learned and takeaways from building the GoTriple Discovery Platform for SSH (Pubmet, 2023)
The TRIPLE project ran from October 2019 to March 2023, with its main outcome being the GoTriple discovery platform. The platform allows users to search and find documents, projects, authors and researchers’ profiles, all related to the Social Sciences and Humanities domain (SSH). GoTriple harvests documents and project metadata from over 1300 sources, published from repositories of research institutes (including Croatia’s HRČAK) and big aggregators, like Isidore, BASE or OpenAIRE.Luca has been actively involved in GoTriple’s implementation, first designing and managing the development of the metadata harvesting and processing platform, SCRE, and later becoming the technical director for the entire TRIPLE project.Ensuring compatibility with the FAIR principles has been one of the main goals of TRIPLE but doing everything right at the first shot is hard. In his presentation, Luca will present the experiences done in the project regarding to adhering to FAIR principles in representingthe digital assets of GoTriple: he will talk about the things that were done right from the start, those which were adjusted “along the way”, without hiding the weak spots that, with the benefit of hindsight, could have been managed differently.This presentation will on the one hand serve to showcase some of the TRIPLE’s valuable contributions in terms of FAIR principles, that can be reused by other SSH related initiatives; on the other hand it will hopefully provide some useful suggestions on how to in general improve metadata FAIRness.